Caracterización faneróptica del gosrater Valencià - M.J. Cárcel Rubio (Archivos de Zootecnia, 2001)
The characteristics of Gos Rater Valenciàdog breed were studied. The spotted coats aremore frequent than the uniforms. The predominantblack-fire coloration often presents white stains.The black color in the truffle and the brown iris isespecially present in the dogs of dark coats.Theform of the eyes is oval, in any case oblique. Allthe animals present parallel skull-facial axes, finelips and erect ears